Knowledge, Attitude, and Practices (KAP) of Human Populations towards Malaria Control in Four Ecoepidemiological Settings in Cameroon - Nelly Armanda Kala Chouakeu; Laura Gilberine Ngingahi; Roland Bamou; Abdou Talipouo; Carmen Sandra Ngadjeu; Marie Paul Audrey Mayi; Edmond Kopya; Parfait Awono-Ambene; Timoléon Tchuinkam; Christophe Antonio Nkondjio (Journal of Tropical Medicine)
Malaria remains a major public health problem in Cameroon. Critical steps to improve disease control include assessing human population adherence to vector control interventions, especially in areas with different cultural backgrounds. The present study seeks to assess the knowledge, attitude, and practices (KAP) of populations towards malaria prevention in four ecoepidemiological settings in Cameroon. A cross-sectional malaria KAP survey was conducted from August to September 2019 in households of the localities of Kaélé, Tibati, Bertoua, and Santchou. A semistructured questionnaire was administered to randomly selected households in the localities. Data recorded were analysed using SPSS v. 20 and MedCalc v14.8.1. A total of 739 households were surveyed. The majority of participants had a secondary level of education (48.71%). A substantial number of participants (over 90%) in all the localities were able to make an accurate association between malaria and mosquito bites. The main sources of information for community members were television sets in Santchou and Tibati and interpersonal conversations in Bertoua and Kaélé. Mosquito nets were the most commonly used protective measure against malaria, and the majority of nets in households came from the free-of-charge mass distribution campaigns organized by the government. Participants with secondary and higher levels of education were more aware of good practices towards malaria control compared to those with a primary level of education. The study revealed that populations’ KAP differed according to localities and culture. More sensitization and education need to be done to improve adherence to prevention programs.